A GUI-driven prototype for synthesizing self-adaptation decision - Azlan Ismail; Susanti Intu; Suzana Zambri (Bulletin of Electrical Engineering and Informatics, 2020)
The ability to ensure an optimal decision is significant for self-adaptive systems especially when dealing with uncertainty. For this reason, a synthesis-driven approach can be used to capture and synthesize a decision that aims to satisfy the multi-objective properties. Assessing the quality of the synthesis-driven approach is challenging, since it involves a set of activities from modeling, simulating, and analyzing the outcomes. This paper presents the design and implementation of a graphical user interface (GUI)-based prototype for assessing synthesis outcome and performance of an adaptation decision. The prototype is designed and developed based on the component-based development approach that is able to integrate the existing and related libraries from PRISM-games model checker for the synthesis engine, JFreeChart libraries for the chart presentation, and Java Universal Network/Graph Framework libraries for the graph visualization. This paper also presents the implementation of the proposed prototype based on the cloud application deployment scenario to illustrate its applicability. This work contributes to provide a fundamental work towards automated synthesis for self-adaptive systems.